ANALYSIS OF RAT PLATELET COUNT AFTER ELECTRICAL EXPOSURE IN ACUTE AND SUBACUTE PHASE OF BURN INJURY - Fransiska Nooril F P H; Ulfa Elfiah; Laksmi Indreswari; Desie Dwi Wisudanti (Jurnal Rekonstruksi dan Estetik)
Highlights: